2011
DOI: 10.1186/1471-2296-12-14
|View full text |Cite
|
Sign up to set email alerts
|

Performance feedback: An exploratory study to examine the acceptability and impact for interdisciplinary primary care teams

Abstract: BackgroundThis mixed methods study was designed to explore the acceptability and impact of feedback of team performance data to primary care interdisciplinary teams.MethodsSeven interdisciplinary teams were offered a one-hour, facilitated performance feedback session presenting data from a comprehensive, previously-conducted evaluation, selecting highlights such as performance on chronic disease management, access, patient satisfaction and team function.ResultsSeveral recurrent themes emerged from participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Yet, regardless of how carefully designed the intervention is, feedback cannot be effective if the intended recipient does not engage. Our findings build upon prior work in Ontario indicating that many physicians do not actively engage in existing A&F initiatives [ 30 – 34 ]. Immediate clinical tasks may take priority, and many physicians, whether working in teams or independently, are struggling to keep up rather than looking for ways to get ahead [ 35 ].…”
Section: Discussionsupporting
confidence: 82%
“…Yet, regardless of how carefully designed the intervention is, feedback cannot be effective if the intended recipient does not engage. Our findings build upon prior work in Ontario indicating that many physicians do not actively engage in existing A&F initiatives [ 30 – 34 ]. Immediate clinical tasks may take priority, and many physicians, whether working in teams or independently, are struggling to keep up rather than looking for ways to get ahead [ 35 ].…”
Section: Discussionsupporting
confidence: 82%
“…At a practice level, Johnston et al observed that primary care teams were receptive of performance feedback and that team members thought that a feedback cycle could improve their organizational culture towards measurement and teamwork. However, findings also revealed that few teams or individuals understood how to use the data they received [ 33 ]. As a result, while many teams cited the promise of D2D’s future potential as a motivator to their participation, the same pressures and moderators may influence motivation to fully participate and eventually implement the A&F program.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study examining a quality improvement intervention in Ontario found that even multidisciplinary primary care teams failed to take action upon receiving feedback reports indicating substandard performance on chronic disease management due to a lack of “performance management skill development” [72]. At the same time, high-cost interventions are unlikely to be scalable or replicated.…”
Section: Methodsmentioning
confidence: 99%